2020
DOI: 10.1002/jcla.23309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of red cell distribution width, mean platelet volume, and cancer antigen 125 detection in endometrial cancer

Abstract: Background Red cell distribution width (RDW) and mean platelet volume (MPV) are considered to be associated with tumors. We investigated the diagnostic value of RDW, MPV, and cancer antigen 125 (CA125), alone or in combination, in the diagnosis of endometrial cancer and endometrial hyperplasia. Methods This study included 144 patients with endometrial cancer (stage I: 32; II: 42; III: 48; and IV: 22), 104 patients with endometrial hyperplasia, and 80 healthy control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“… 28 Other studies have examined lung, bladder, endometrial, ovarian, and thyroid cancers. 29–33 These results combined with ours indicate that RDW may be a universal factor in tumors. The mechanism may be as follows.…”
Section: Discussionsupporting
confidence: 73%
“… 28 Other studies have examined lung, bladder, endometrial, ovarian, and thyroid cancers. 29–33 These results combined with ours indicate that RDW may be a universal factor in tumors. The mechanism may be as follows.…”
Section: Discussionsupporting
confidence: 73%
“…Eight studies relating MPV to endometrial cancer were identified, including 1707 patients from China and Turkey [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] ( Table 4 ). In all studies, including a control group, MPV was increased in cancer versus healthy patients [ 66 , 67 , 69 , 70 , 71 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 In recent years, many studies have shown that RDW is associated with the prognosis of breast cancer, 11 ovarian cancer 12 and gastric cancer. 13 Zhang et al 18 showed associated with the stage of EC, with a higher level of RDW-CV was a poor prognostic factor for EC. In contrast, there was no significant difference in RDW-SD levels between patients with early and advanced EC, and the mechanisms underlying this outcome need to be further investigated.…”
Section: Discussionmentioning
confidence: 98%
“… 16 In recent years, many studies have shown that RDW is associated with the prognosis of breast cancer, 11 ovarian cancer 12 and gastric cancer. 13 Zhang et al 18 showed that RDW was an independent risk factor for EC and had a high diagnostic value. Few relevant studies have been conducted on the RDW of EC, and most current studies focus only on RDW, without subdividing RDW into RDW-CV and RDW-SD.…”
Section: Discussionmentioning
confidence: 99%